Diffusion-Related SOFC Stack Degradation. (30th May 2017) - Menzler, Norbert H.; Beez, Alexander; Grünwald, Nikolas; Sebold, Doris; Fang, Qingping; Vaßen, Robert
Abstract : As part of two different stack tests with four-plane short stacks and their intensive post-test characterization, two varying diffusion-related degradation mechanisms were investigated. The first was a short-term test ( 1250h) with two different chromium evaporation protection layers on the air-side metallic interconnect and frame and the second was a long-term endurance test ( 35, 000h). For the first stack, two planes were coated with a manganese oxide layer applied by wet powder spraying (WPS), while the other two planes were coated with a manganese–cobalt–iron spinel layer by atmospheric plasma spraying (APS). The voltage loss in the planes with a WPS-coated interconnect was markedly higher than in those coated by means of APS. Finally, it was shown that the microstructure of the layers plays a key role in minimizing Cr evaporation. In this stack, gas-phase diffusion prevails over degradation. In the long-term stack, severe degradation due to solid-state manganese diffusion was observed. This paper draws an interaction hypothesis.